A full scale experimental study of prestressed stayed columns. (1st October 2015) - Serra, Miguel; Shahbazian, Ashkan; da Silva, Luís Simões; Marques, Liliana; Rebelo, Carlos; da Silva Vellasco, Pedro Colmar Gonçalves
Graphical abstract: Highlights: First experimental investigation on 12 m spatial stayed column with high initial pretension. Development of experimental setup. Comparison of experimental results with available analytical methods. Abstract: This paper presents the results of an experimental study on 12 m prestressed stayed columns. In total, 44 tests were carried out to investigate the compressive strength and behaviour of such systems by varying column cross-section geometry, diameter of cables, initial pretension level of stays and steel grade. The details of material testing for both steel and cable, and the compressive strength of each specimen including a detailed analysis of results for further numerical and analytical investigations are presented. The applicability of available analytical and design methods for determining the elastic buckling load and the load carrying capacity of stayed columns was assessed. The results provide detailed data on the behaviour of realistic PSSC and highlight the importance of the imperfections and the benefits of such systems.